Produksi Telur dan Income Over Feed Cost (IOFC) Puyuh Petelur (Coturnix-coturnix japonica) yang Diberi Tepung Bawang Putih (Allium sativum) - Arthadinata, S N; Rahayu, N; Frasiska, N (PETERPAN (Jurnal Peternakan Terapan), 2025)
The purpose of this research is to determine the effect of garlic flour (Allium sativum) on laying quail (Coturnix-coturnix japonica) on egg production and Income Over Feed Cost (IOFC). This research was conducted on January 22, 2024 – February 22, 2024 in the rearing cage of the Animal Husbandry Study Program, Perjuangan Tasikmalaya University. The research material’s is 60 productive female quails aged 70 days with an average body weight of 150 grams/head, commercial feed, and garlic flour. The method used in this study is an experimental method using a Complete Random Design (RAL) of 5 treatments and 4 replicates. The treatment of the study was the provision of commercial feed and additional garlic flour, namely P0 = addition of 0% garlic flour, P1 = addition of 2% garlic flour, P2 = addition of 4% garlic flour, P3 = addition of 6% garlic flour, and P4 = addition of 8% garlic flour. The data is analyzed using ANOVA, if there is a real or very real difference, then it is continued with the Duncan Multiple Distance Test. The results showed that the administration of garlic flour (Allium sativum) had no real effect (P>0.05) on egg production and Income Over Feed Cost (IOFC). The highest average values of QDP and QHP were found at the level of 8% while the average egg mass and IOFC were highest at the level of 6% of garlic flour administration. The conclusion of this study is that the addition of garlic flour (Allium sativum) showed no significant difference of Quail Day Production (QDP), Quail House Production (QHP), Egg mass, and Income Over Feed Cost (IOFC) of Quail Eggs (Coturnix-coturnix japonica)